1979
DOI: 10.1111/j.1439-0418.1979.tb02477.x
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity tests on Bacillus thuringiensis and B. cereus isolated from resting larvae of Pectinophora gossypiella (Lepidoptera, Gelechiidae)

Abstract: Four bacterial strains, isolated from sick or dead resting larvae of Pectinophora gossypiella, were tested against larvae of this pest. In the first test, mortality rates among larvae injected with saline suspensions of three Bacillus strains, were as follows: Bacillus thuringiensis var. finitimus 100%, B. t. var. thuringiensis 92 % and B. cereus 48 %, as compared to mortality of 8 % in the control. In the other test, injection of B. polymyxa, induced no higher mortality among treated larvae than in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Also, B. thringiensis, S. avermecti and Micrococcus sp. were isolated from cotton bollworm larvae ( Abul-Nasr et al, 1979, Bekheit et al, 1995and El-Barbary, 2006. Laboratory experiments indicated that pathogenic bacteria, B. thurigiensis especially strain I had the highest pathogenicity to the pink , spiny and American bollworms, while S. avermecti ranked second in the order of activity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, B. thringiensis, S. avermecti and Micrococcus sp. were isolated from cotton bollworm larvae ( Abul-Nasr et al, 1979, Bekheit et al, 1995and El-Barbary, 2006. Laboratory experiments indicated that pathogenic bacteria, B. thurigiensis especially strain I had the highest pathogenicity to the pink , spiny and American bollworms, while S. avermecti ranked second in the order of activity.…”
Section: Discussionmentioning
confidence: 99%